PENELITIAN DAN RANCANGAN OPTIMAL TURBIN PENGGERAK TEROWONGAN ANGIN SUBSONIK SIRKUIT TERBUKA LAPAN - Atmadi, Sulistyo (Indonesian Journal of Aerospace, 2004)
In an effort to improve flow condition and flow speed up to 50 m per s inside LAPAN Subsonic Wind Tunnel, an existing power system and turbine has to be redesigned. Specifications for these requirments have been determined and calculated for the required power and aerofoil type and their dimensions. A method based free vortex design was used to get optimal result. The optimization result produced a turbine with 3 m diameter, with 10 blades, 1.5 m hub diameter. A D RAF PROPELLER aerofoil type was used to produce 230 HP power and 1824 Nm torque, with an efficience 89 percent. This result was considered both technically and economically.